Anti-Human Herpesvirus 6A/B IgG Correlates with Relapses and Progression in Multiple Sclerosis - Ortega-Madueño, Isabel (Public Library of Science, 2014)
OBJECTIVE: To analyze the titers of the IgG and IgM antibodies against human herpesvirus 6A/B (HHV-6A/B) in multiple sclerosis (MS) patients treated with different disease modified therapies (DMTs) along two-years of follow-up. METHODS: We collected 2163 serum samples from 596 MS; for 301 MS patients a 2-years follow-up was performed. Serum samples of 337 healthy controls were also analyzed. Anti-HHV-6A/B IgG and IgM were analyzed by ELISA (Panbio). RESULTS: We found that 129/187 (69.0%) MS patients with a decrease of the anti-HHV-6A/B IgG titers after 2-years with DMTs were free of relapses and progression vs. 46/113 (40.7%) of MS patients with an increase of the anti-HHV-6A/B IgG titers (p = 0.0000015); the higher significance was found for natalizumab. Furthermore, we found that anti-HHV-6A/B IgG titers reached their highest value two weeks before the relapse (p = 0.0142), while the anti-HHV-6A/B IgM titers reached their highest value one month before the relapse (p = 0.0344). CONCLUSION: The measurement of the anti-HHV-6A/B IgG titers could be a good biomarker of clinical response to the different DMTs. The increase of the anti-HHV-6A/B IgG and IgM titers predicts the upcoming clinical relapses. However, further longitudinal studies are needed to validate these results.